Efektivitas Pembelajaran Stem Terhadap Kemampuan Pemahaman Konsep Matematika Siswa - Urpani, Denis; Kristayulita, Kristayulita (Jurnal of Math Tadris, 2024)
This study aims to determine the effectiveness of STEM learning on the ability to understand students' mathematical concepts on composition function material and inverse functions. This research approach is a quantitative approach and a type of quasi-experimental research with a form of one group pretest-posttest design. The sample of this study was class XB MA Tarbiyatul Mustafid students totaling 25 students. The sampling technique in this study was carried out by cluster sampling. Research instruments used in research are tests, documentation and observation sheets. The data analysis technique uses paired sample t-test. The results of the paired t-test that Ho was rejected showed that the average ability to understand students' mathematical concepts after being given STEM learning was higher than before it was given so that it can be concluded that STEM learning is effective on students' ability to understand mathematical concepts.